(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2009)
In the present study, five helminth parasite species from two taxonomic groups were identified from Long-Evans (Rattus norvegicus Berkenhout, 1769). The cestodes were Vampirolepis nana Siebold, Hymenolepis diminuta Rud and nematodes were Citellina dispar Prendel, Heterakis spumosa Schneider and Syphacia muris Yamaguti. C. dispar is a new finding in Bangladesh. The highest prevalence of H. diminuta was recorded but the highest intensity was recorded in V. nana. The prevalence and intensity of V. nana was 56.25% and 65.11±13.23; H. dimisnuta was 72.92% and 4.37±0.89; C. dispar was 62.50% and 19.63 ±2.10; H. spumosa was 66.67% and 9.06±1.85; and S. muris was 64.58% and 24.65±2.60 respectively. Differences in prevalence and intensity due to sexes and seasons were also evaluated. Key words: Cestodes, Nematodes, Helminth, Prevalence, Intensity. doi: 10.3329/bjsir.v44i1.2718 Bangladesh J. Sci. Ind. Res. 44(1), 109-116, 2009